Crafting and Executing Strategy: The Quest for Competitive Advantage: Concepts and Cases - E.Gamble John (McGraw-Hill, 2007)
Thompson, Strickland and Gambles’, CRAFTING AND EXECUTING STRATEGY, 16e presents the latest research findings from the literature and cutting-edge strategic practices of companies have been incorporated to keep step with both theory and practice. The chapter content continues to be solidly mainstream and balanced, mirroring both the best academic thinking and the pragmatism of real-world strategic management.